2017
DOI: 10.1039/c6ra27104a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal on the methanol to aromatics conversion over modified ZSM-5 in the presence of carbon dioxide

Abstract: Interaction of catalysts' active sites with CO2 affected the aromatics yield of the MTA reaction over modified catalysts in a CO2 atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…Conte et al 11 observed a signicant decrease in alkenes selectivity while Li et al 13 saw a small reduction in alkenes selectivity. With regard to the p-X byproduct, on all Zn-modied HZSM-5 catalysts, the purity of p-X in xylenes (p-X/X) was around 24.0% except for the 72.4% by Xu et al 10 Silica deposition on HZSM-5 would shi the undesirable m-X, o-X, and nine-or more-nine-carbon higher aromatics (A9+) to the more desirable p-X, as shown in the appendix, Table 7. However, changes in the selectivities for alkanes, alkenes, and P were quite different in these studies.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Conte et al 11 observed a signicant decrease in alkenes selectivity while Li et al 13 saw a small reduction in alkenes selectivity. With regard to the p-X byproduct, on all Zn-modied HZSM-5 catalysts, the purity of p-X in xylenes (p-X/X) was around 24.0% except for the 72.4% by Xu et al 10 Silica deposition on HZSM-5 would shi the undesirable m-X, o-X, and nine-or more-nine-carbon higher aromatics (A9+) to the more desirable p-X, as shown in the appendix, Table 7. However, changes in the selectivities for alkanes, alkenes, and P were quite different in these studies.…”
Section: Introductionmentioning
confidence: 91%
“…In the literatures, the HZSM-5 used for methanol to aromatics contained high amount of Brønsted acid sites (BAS) compared to that of Lewis acid sites (LAS). 3,9,10,13 Zn impregnation on such HZSM-5 decreased BAS and increased LAS significantly. 3,9,10,13 This resulted in an increase in the aromatics selectivity and a decrease in alkanes selectivity.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…[1][2][3] HZSM-5 zeolite is regarded as the most appropriate catalytic-material for this process, because of its adjustable acidic properties, high hydrothermal stability and regular three-dimensional 10-ring pore matching with the light aromatic molecules. [1][2][3] HZSM-5 zeolite is regarded as the most appropriate catalytic-material for this process, because of its adjustable acidic properties, high hydrothermal stability and regular three-dimensional 10-ring pore matching with the light aromatic molecules.…”
Section: Introductionmentioning
confidence: 99%